Molecular genetics in the National Health Service in Britain. Issue 4 (April 1989) - Harris, R; Elles, R; Craufurd, D; Dodge, A; Ivinson, A; Hodgkinson, K; Mountford, R; Schwartz, M; Strachan, T; Read, A
Abstract : A recent report from the Departments of Health draws attention to the value of DNA diagnosis for inherited diseases and the need for planning these services in the National Health Service. There is great potential for preventive medicine, but a major immediate benefit is the newfound ability to exclude the carrier state in many people at risk and to protect fetuses from abortion when, as in most cases, they are shown to be normal by DNA tests. However, the widespread application of these new techniques requires prior evaluation and general acceptance. This will only be obtained after public debate, education of professionals and the population, and the establishment of adequate non-directive genetic counselling services. Some of the points to be considered in setting up molecular genetics laboratories are described.